Sukuk versus bonds: New evidence from the primary market - Nawaf Al-Maskati (Borsa İstanbul Review, 2022)
We use a propensity score matching procedure to compare the returns of sukuk and conventional bond issuances in the primary market in the period 2000-2021. The results of our analysis show that sukuk are issued at lower overall coupon levels than conventional bonds. We find that the difference is between -11 and -28 basis points, depending on the matching technique used. Our analysis also shows that the difference is larger in corporate issuances than noncorporate issuances. We believe that these findings can be explained by the higher demand for sukuk issuances due to the limited investment universe available to Islamic investors.
Keywords: E43; G12; G21; 330; Conventional bonds; Islamic debt; Primary market; Propensity score; Return spreads; Sukuk